How to treat multiple myeloma: a representative multicentre treatment survey - Knauf, Wolfgang; Kellermann, Lenka; Poenisch, Wolfgang; Einsele, Hermann; Straka, Christian; Frohn, Claas; Goldschmidt, Hartmut (Oncology research and treatment, 2010)
The present survey was undertaken to gain insights in the changes of disease management of multiple myeloma (MM) over time and the implementation of new guidelines into daily practice.